The Grammatical Cohesion in Indonesian Paragraph - Praptomo Baryadi Isodarus (International Journal of Social Service and Research (IJSSR), 2023)
The study examines the grammatical unit that becomes the means for each type of grammatical cohesion in Indonesian paragraphs. The object of this study is the grammatical cohesion in a paragraph of Indonesian language. The research problems are the type of grammatical cohesion in Indonesian language paragraph and the grammatical unit that mean to every grammatical cohesion itself. This study uses a theory that is proposed by Halliday and Hassan (1976). The data obtained from the news discourse, exposition discourse, narrative discourse, and procedural discourse found in online and offline media. The data collected using observational method and then to be analyzed using distributional method. The distributional method is applied using substitution technique and marker reading technique. The results of this study state that grammatical cohesion in Indonesian paragraphs consists of reference cohesion, substitution cohesion, ellipsis cohesion, and conjunction cohesion.